Facework by global brands across Twitter and Weibo. (December 2018) - Li, Chaoyuan; Wu, Doreen Dongying
Abstract: Applying a micro-analytical form of discourse analysis to a set of microblogging record over a three-month period, the study examines how ten top global brands utilize linguistic resources and strategies to build positive and socially acceptable images with the public across two significant social media platforms, i.e., with the English speaking public on Twitter and with the Chinese speaking public on Weibo. In the process of the examination, the notions of face and facework from interactional linguistics are utilized and further defined. It is found that impression management by these global corporations on social media is characterized by duality of facework: on one hand, global brands promote their corporate assets, as evidenced in the use of speech acts such as disclosing corporate information and broadcasting corporate products and campaigns; on the other hand, they build solidarity with their followers, as evidenced in the use of speech acts such as greeting, directing, expressing, sharing, and retweeting. Finally, the study points to the emergence of a global culture on social media and concludes with a glocalization perspective for further studies of corporate communication practice in the age of digitalization.